BOKOL MONGONG-KELI REPIS DALAM KONSEPSI TANGGUNG JAWAB EMMANUEL LEVINAS - Wele, Marianus (Studi Budaya Nusantara, 2020)
This study examines the local wisdom in the tradition of Riung cultural of Bokol Mongong-Keli Repis. Bokol Mongong-Keli Repis implies the understanding of maintaining the unity that has existed in order to remain sustainable and to knit again which had been scattered and one another "far apart." Bokol Mongong-Keli Repis as a material object will be examined with a formal object that is the conception of responsibility Emmanuel Levinas. This research method uses qualitative phenomenology with some steps: that is doing a description, interview, and interpretation. The results of the research found that Bokol Mongong-Keli Repis is (1) an expression of the desire to unite together and make peace; (2) has a content of a rational function; (3) respecting others lyan; (4) responsibilities in the life together; and (5) there is love as a binder. The conception of responsibility can be a recommendation as a basis for maintaining relations in the tradition of Riung cultural.